Prevalence of pharmacotherapy in the department of paediatric dentistry - Paudel, KR; Sah, NK; Jaiswal, AK (Kathmandu University Medical Journal, 2010)
Background: Pharmacotherapy plays important role in the management of paediatric dental patients in the department of paediatric dentistry. Many children at their early age suffer from different kinds of dental conditions such as acute and chronic irreversible pulpitis, acute and chronic alveolar abscesses, dentoalveolar and vestibular abscesses, etc along with physiological tooth movement that requires professional help for dental treatment. Treatment of such conditions most frequently requires pharmacotherapy as an either adjunct to dental therapeutic procedure or as a monotherapy. Objective: To assess the prescribing patterns vis-a-vis generic or trade name, generic class, dosage form, route, frequency, duration, number of drugs per patient, cost and indication of drug therapy, patterns of dental treatment and Frankl's behavioral rating. Materials and methods: Prescriptions of 200 paediatric dental patients undergoing dental treatment in the department of paediatric dentistry were analyzed prospectively for a period of six months in a dental teaching hospital. Results: 133 (56.5%) patients were males and 87 (43.5%) females and age group 6-10 years was the most frequent group (70%, P=0.0000000) and all the patients received pharmacotherapy. Total numbers of 357 drugs were prescribed. Out of them, 212 (59.4%, P=0.0000008) were analgesic agents, 133 (37.3%) antimicrobial agents (AMAs) and 12 (3.3%) other drugs. Extended spectrum Penicillins were the most commonly prescribed (90.2%) AMA followed by Metronidazole (9.8%). 247 drugs (69.2%, P=0.0000000) were prescribed by trade names. 60% (P=0.0000002) drugs were prescribed in the form of tablet or capsule followed by syrup 37% and administered entirely through oral route. Percentage of patients receiving three drugs, two drugs and one drug was 13.5%, 56.5% (P=0.0000000) and 30% respectively and one patient received on average 1.78 medicines. 133 patients (56.5%, P=0.0000000) received both AMA and analgesic agent. Minimum to maximum number of days for pharmacotherapy were 2 to 15 and highest frequency was up to four times a day. Cost of medicines was in the range of 10-150 Nepalese Rupees. Chronic irreversible pulpitis was the commonest diagnosis (28%) and extraction (92.5%) was the commonest dental procedure. Frankl's behaviour rating showed that 78.5% (P=0.0000000) patients had positive attitude towards the dental procedures. Conclusion: Findings of the study suggest that pharmacotherapy is the mainstay in therapy to treat the paediatric dental patients along with dental procedures either to control the dental pain or odontogenic infection. Age group 6-10 years, chronic irreversible pulpitis and dental extraction are the commonest age group, diagnosis and dental procedure respectively in the department of paediatric dentistry. Analgesic (non-steroidal anti-inflammatory drugs- Nimesulide, Ibuprofen and Paracetamol) and Amoxicillin are the most frequently prescribed drugs mostly in the solid dosage forms in trade names via oral route. Duration of pharmacotherapy ranges from 2 to 15 days with highest frequency being up to 4 times a day. Majority of the patients are manageable without any behavioural modification technique- physical or pharmacological. Key words: Dentistry; Frankl's behaviour rating; Paediatric; Pharmacotherapy; Prescription DOI: 10.3126/kumj.v8i2.3556 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 190-194